Two sides of the same coin: recruitment performance and perceived workload in primary care trials-insights from the AgeWell.de study - Linda Sanftenberg; Robert Philipp Kosilek; Lorenz Birnberger; Hannah Schillok; Felix Wittmann; Melanie Luppa; Anne Blawert; Melanie Boekholt; Christian Brettschneider; Hans-Helmut König; Alexander Bauer; Solveig Weise; et al. (BMC Primary Care)
Abstract Background Recruitment through general practitioners (GPs) is a key challenge in primary care trials. Understanding how individual, practice, and regional characteristics affect recruitment and perceived workload could help optimize participation strategies. This study aims to identify barriers and facilitators to patient recruitment within the AgeWell.de dementia prevention trial. Methods We analysed publicly available data on GPs participating in the AgeWell.de trial, including their sociodemographic characteristics, practice structures, and socioeconomic indicators of their practice locations, alongside recruitment and survey data. We used correlation analysis and uni- and multivariable regression models to explore determinants of study engagement in terms of recruitment performance and perceived workload. Results Among 120 participating GPs, a total of 1,173 patients were recruited, though contributions varied widely. The top 20% of recruiters (Q5) accounted for 42.1% of all participants, while the lowest quintile (Q1) recruited just 3.2%. GPs with a doctorate degree recruited more patients (IRR = 1.45, p < 0.05). Higher perceived workload was linked to increased recruitment engagement (IRR = 1.30, p < 0.1). In contrast, larger practice teams were associated with lower perceived workload (OR = 0.71, p < 0.1). Conclusion GP recruitment performance and perceived workload are closely linked, influenced by both individual research interest and structural support. The disproportionate recruitment burden among a small subset of GPs highlights the need for strategies to engage low recruiters and support high performers. Strengthening practice-based research networks, could help make research involvement more feasible for a wider range of GPs. Trail registration: German Clinical Trials Register (DRKS; trial identifier: DRKS00013555); Date of Registration: 2017-12-07.